Expertise of the modern reproductive situation in Belarus - Zlotnikov, Anatoly G. (Journal of the Belarusian State University. Sociology, 2019)
The state of the reproductive processes in the Republic of Belarus and the impact of the financial reform on the changes in the demographic processes of Belarus in 2017 are analyzed. The results of sociological studies carried out within the framework of demographic monitoring, which characterize the interaction of demographic processes with social spheres and social institutions are outlined. The role of sociological science in comprehending the demographic situation in Belarus is justified.